2019
DOI: 10.3390/cancers11050711
|View full text |Cite
|
Sign up to set email alerts
|

Novel Thienopyrimidine Derivative, RP-010, Induces β-Catenin Fragmentation and Is Efficacious against Prostate Cancer Cells

Abstract: Thienopyrimidines containing a thiophene ring fused to pyrimidine are reported to have a wide-spectrum of anticancer efficacy in vitro. Here, we report for the first time that thieno[3,2-d]pyrimidine-based compounds, also known as the RP series, have efficacy in prostate cancer cells. The compound RP-010 was efficacious against both PC-3 and DU145 prostate cancer (PC) cells (IC50 < 1 µM). The cytotoxicity of RP-010 was significantly lower in non-PC, CHO, and CRL-1459 cell lines. RP-010 (0.5, 1, 2, and 4 µM)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 72 publications
0
10
0
Order By: Relevance
“…Human primary epithelial gingival keratinocytes (HPK), and normal colon fibroblast CRL1459 cells were purchased from American Type Culture Collection (ATCC#PCS-200-014, and ATCC#CCD-18Co—CRL-1459, respectively, Manassas, VA, USA). These cells were grown as an adherent monolayer with Dulbecco’s Modified Eagle’s Medium (Corning, Tewksbury, MA, USA) supplemented with 10% fetal bovine serum (Biofluids Technologies, Port Richey, FL, USA), 2 mM of L-glutamine and 100 U/mL of penicillin and 100 µg/mL of streptomycin (Thermo Fisher Scientific, Inc., Waltham, MA, USA), as previously described [ 42 ]. HPKs cells were cultured in dermal cell basal medium (ATCC# PCS-200-030) supplemented with factors from Keratinocyte growth kit (ATCC# PCS-200-040) as per manufacture’s protocol.…”
Section: Methodsmentioning
confidence: 99%
“…Human primary epithelial gingival keratinocytes (HPK), and normal colon fibroblast CRL1459 cells were purchased from American Type Culture Collection (ATCC#PCS-200-014, and ATCC#CCD-18Co—CRL-1459, respectively, Manassas, VA, USA). These cells were grown as an adherent monolayer with Dulbecco’s Modified Eagle’s Medium (Corning, Tewksbury, MA, USA) supplemented with 10% fetal bovine serum (Biofluids Technologies, Port Richey, FL, USA), 2 mM of L-glutamine and 100 U/mL of penicillin and 100 µg/mL of streptomycin (Thermo Fisher Scientific, Inc., Waltham, MA, USA), as previously described [ 42 ]. HPKs cells were cultured in dermal cell basal medium (ATCC# PCS-200-030) supplemented with factors from Keratinocyte growth kit (ATCC# PCS-200-040) as per manufacture’s protocol.…”
Section: Methodsmentioning
confidence: 99%
“…Methyl 2-amino-4-(diethylamino)-thieno-[2,3-d]-pyrimidine-6-carboxylate, abbreviated as tpc within the text, has been selectively chosen in order to rationally design a neutral complex containing the cod hydrophobic moiety on the metal core. This organic compound (tpc) belongs to the class of thieno- [2,3-d]pyrimidines that displays interesting biological abilities, [24] such as anticancer, [25,26] analgesic, [27] antimicrobial, [28] kinase receptor inhibitors, [29] and anti-inflammatory. [30] Therefore, in order to achieve the above mentioned goals, we set out to synthesize a model compound, target molecule (prototype), so as to collect preliminary results about its action against PAF-induced aggregation both in WRPs and in human platelets.…”
Section: Introductionmentioning
confidence: 99%
“…The flipped anionic PS binds to the Ca 2+ -dependent phospholipid-binding protein, annexin V [ 49 ]. We discovered and reported several potent apoptosis-inducing compounds [ 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ]. In this study, the result of our morphological studies in MDA-MB-231 cells after incubation with our lead compounds, 4g and 4i, indicated that apoptosis was occurring ( Figure 3 A).…”
Section: Resultsmentioning
confidence: 99%